Optimization of the Power Conversion Efficiency of CsPbIxBr3−x-Based Perovskite Photovoltaic Solar Cells Using ZnO and NiOx as an Inorganic Charge Transport Layer - Hyojung Son; Byoung-Seong Jeong (Applied Sciences, 2022)
In this study, we analyzed the maximum power conversion efficiency (PCE) of a photovoltaic cell with an ITO/ZnO/CsPbIxBr3−x/NiOx/Au structure, using ZnO and NiOx as the inorganic charge transport layers and CsPbIxBr3−x as an absorption layer. We optimized the thickness of each layer and investigated the effects of the defect density and interface defect density. To achieve the highest PCE, the optimal thicknesses were 300 nm for the electron transport layer (ZnO), 60 nm for the hole transport layer (NiOx), and 1000 nm for the absorption layer. The absorber defect density was maintained at approximately 1015 cm−3, and the interface defect density was approximately 1011 cm−3. The highest PCE obtained through optimization of each of these factors was 23.07%. These results are expected to contribute to the performance optimization of perovskite solar cells that use inorganic charge carrier transport layers.